2020
DOI: 10.1186/s12885-019-6408-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the NEK family in normal and cancer tissue: an immunohistochemical study

Abstract: Background: The NEK serine/threonine protein kinases are involved in cell cycle checkpoints, DNA damage repair, and apoptosis. Alterations in these pathways are frequently associated with cell malignant cellular transformations. Thyroid cancer is the most common malignant tumour in the endocrine system. Despite good treatment methods, the number of cases has increased significantly in recent years. Here, we studied the expression of NEK1, NEK2, NEK3, and NEK5 in different types of normal and malignant tissues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…In a recently published paper by our group, a direct link between NEK1 and thyroid cancer was observed [67]. Tissue microarray analysis revealed increased expression of NEK1 in classical and follicular variants of papillary thyroid cancer, allowing us to use these levels of expression to discriminate the malignancies with high specificity and sensitivity.…”
Section: Nek1mentioning
confidence: 96%
See 2 more Smart Citations
“…In a recently published paper by our group, a direct link between NEK1 and thyroid cancer was observed [67]. Tissue microarray analysis revealed increased expression of NEK1 in classical and follicular variants of papillary thyroid cancer, allowing us to use these levels of expression to discriminate the malignancies with high specificity and sensitivity.…”
Section: Nek1mentioning
confidence: 96%
“…Additionally, NEK3 overexpression is related to poor overall survival [129]. Similarly, an analysis of papillary thyroid carcinomas and follicular thyroid carcinomas revealed that the expression of NEK3 is stronger in tall-cell papillary thyroid cancer, with the highest levels being observed in patients with metastases [67].…”
Section: Nek3mentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of Nek1 in glioma tissue correlated with the clinical grade and Karnofsky performance scale, and was significantly associated with a poor OS, while an siRNA-mediated KD of Nek1 sensitized glioblastoma cells to the drug temozolomide [23]. Nek1 expression was elevated in thyroid tumors with multifocality and in patients with lymph node metastasis [44]. Nek1 is further reported to be associated with a decreased sensitivity to DNA damaging agents in renal cell carcinomas [45] and to be part of a 12-gene tumor signature to predict progression of non-invasive to muscle-invasive bladder cancer [24].…”
Section: Discussionmentioning
confidence: 96%
“…Our results about the association of Nek1 with the clinical outcome, its impact on clonogenic survival and tumor growth in vivo indicate the protein to represent a valuable target for radiation sensitization. In addition, given an overexpression of multiple members of the Nek family in human malignancies and overlapping functional properties [16,44], the entire family should be considered for use in pharmacological approaches to increase radiation or chemotherapy response in anti-cancer treatment.…”
Section: Discussionmentioning
confidence: 99%